Cloned pig fetuses exhibit fatty acid deficiency from impaired placental transport. Issue 11 (25th July 2019) - Ao, Zheng; Wu, Xiao; Zhou, Jun; Gu, Ting; Wang, Xingwang; Shi, Junsong; Zhao, Chengfa; Cai, Gengyuan; Zheng, Enqin; Liu, Dewu; Wu, Zhenfang; Li, Zicong
Abstract: Cloned pig fetuses produced by somatic cell nuclear transfer show a high incidence of erroneous development in the uteri of surrogate mothers. The mechanisms underlying the abnormal intrauterine development of cloned pig fetuses are poorly understood. This study aimed to explore the potential causes of the aberrant development of cloned pig fetuses. The levels of numerous fatty acids in allantoic ﬂuid and muscle tissue were lower in cloned pig fetuses than in artificial insemination‐generated pig fetuses, thereby suggesting that cloned pig fetuses underwent fatty acid deficiency. Cloned pig fetuses also displayed trophoblast hypoplasia and a reduced expression of placental fatty acid transport protein 4 (FATP4), which is the predominant FATP family member expressed in porcine placentas. This result suggested that the placental fatty acid transport functions were impaired in cloned pig fetuses, possibly causing fatty acid deficiency in cloned pig fetuses. The present study provides useful information in elucidating the mechanisms underlying the abnormal development of cloned pig fetuses. Abstract : The cloned pig fetuses underwent fatty acid deficiency. The placental fatty acid transport functions were impaired in cloned pig fetuse.